THE EFFECTIVENESS OF A FLOOD WARNING: A CASE STUDY OF TS FRED IN WNC - Elizabeth Cox (UNC Test Journal, 2024)
This study exposes a need for empowerment in Western North Carolina’s (WNC) response capacity to emergency warnings. A rapidly changing climate is causing an increase in extreme flooding events in WNC, like in the case of tropical storm (TS) Fred, where multiple warnings and alerts were issued. Preparing vulnerable communities is critical to the path of response capacity. Therefore, to understand how to improve the efficacy of emergency alerts, I locate WNC’s most vulnerable populations by utilizing information from the Social Vulnerability Index (SVI) and the Climate Resilience Estimate (CRE). Then, using QGIS, I overlay the flood risk data and compare the overlap to actual impacts. Research like this across the region can support emergency managers, decision-makers, and governing authorities in their future planning and communication processes. Additionally, a survey presents evidence that explores the response capacity of warning recipients. This research conveys that people frequently do not know how to respond, therefore the warnings suffer in efficacy. The problem is exacerbated by compounding warnings with confusing instructions, for example during TS Fred, when multiple warnings to stay indoors were suddenly followed by an evacuation order. Through increased collaboration, governing authorities and the general public can improve methods of agency, possibly avoiding many of the adverse impacts of severe flooding events.